Triterpene constituents from the fruits of Cyclocarya paliurus and their anti-HIV-1 IIIB activity - Tu, Wen-Chao; Luo, Rong-Hua; Yuan, En; Sakah, Kaunda-Joseph; Yang, Quan-Yu; Xiao, Wei-Lie; Zheng, Yong-Tang; Liu, Mei-Feng (Natural product research, 2023)
Four new norceanothane-type triterpenes, cyclopalin ( ), and sixteen known compounds ( ) were obtained from the fruits of . Their structures were determined by spectroscopic data, experimental electronic circular dichroism (ECD) and X-ray single crystal analyses. All isolated compounds were assayed for their anti-HIV-1 activity. Compound exhibited potent anti-HIV-1 activity with an EC value of 1.32 μM (SI = 151.52).